2014
DOI: 10.1038/nature13478
|View full text |Cite
|
Sign up to set email alerts
|

The role of hepatic lipids in hepatic insulin resistance and type 2 diabetes

Abstract: Non-alcoholic fatty liver disease and its downstream sequelae, hepatic insulin resistance and type 2 diabetes, are rapidly growing epidemics, which lead to increased morbidity and mortality rates, and soaring health-care costs. Developing interventions requires a comprehensive understanding of the mechanisms by which excess hepatic lipid develops and causes hepatic insulin resistance and type 2 diabetes. Proposed mechanisms implicate various lipid species, inflammatory signalling and other cellular modificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
759
6
12

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 957 publications
(803 citation statements)
references
References 120 publications
(129 reference statements)
26
759
6
12
Order By: Relevance
“…It was previously suggested that increased adipose tissue lipolysis is an important source of FFA promoting hepatic lipid accumulation. 8 In addition, TNFa stimulates lipolysis in adipocytes. 16 Hence, increased TNFa expression in mesenteric WAT may have promoted FFA release in HFD RF mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was previously suggested that increased adipose tissue lipolysis is an important source of FFA promoting hepatic lipid accumulation. 8 In addition, TNFa stimulates lipolysis in adipocytes. 16 Hence, increased TNFa expression in mesenteric WAT may have promoted FFA release in HFD RF mice.…”
Section: Discussionmentioning
confidence: 99%
“…7 However, in contrast to short-term HFD-induced liver steatosis, adipose tissue lipolysis is thought to be the main source of circulating FFA leading to liver fat accumulation upon chronic caloric surplus. 8 Accordingly, lipolytic activity in mesenteric adipose tissue may be of high relevance in the latter, as mesenteric fat is mainly drained via the portal vein to the liver. 9 In support of such notion, increased visceral lipolysis was linked to obesity-induced fat accumulation in morbidly obese humans.…”
Section: Introductionmentioning
confidence: 99%
“…However, whether insulin resistance promotes hepatic lipid accumulation or whether NAFLD initiates insulin resistance remains unclear to date. Nevertheless, it appears that skeletal muscle insulin resistance can cause insulin resistance in other tissues (Jornayvaz and Shulman, 2012;Perry et al, 2014). For instance, deletion of the muscle insulin receptor in mice (MIRKO mice) results in the development of insulin resistance in other organs, possibly through substrates redistribution toward adipose tissue (Kim et al, 2000b).…”
Section: Ectopic Fat Accumulation Promotes Hepatic Insulin Resistancementioning
confidence: 99%
“…On this point, it should be noted that the Stender et al 2 non invasively assessed hepatic triglyceride, a neutral lipid that does not trigger hepatic insulin resist ance or immune activation. Rather, it is the combin ation of ceramides, phospholipids, free fatty acids, free cholesterol and diacyl glycerol that mediates the harmful effects that drive steatohepatitis 5 . Given data pub lished this year that establishes a direct role for PNPLA3 in the activ ation of hepatic This BMI-gene interaction seems to be specific to hepatic traits.…”
mentioning
confidence: 99%